Major antigen and paramyosin proteins as candidate biomarkers for serodiagnosis of canine infection by zoonotic Onchocerca lupi. - Maria Stefania Latrofa; Giuseppe Palmisano; Giada Annoscia; Ciro Leonardo Pierri; Ramaswamy Chandrashekar; Domenico Otranto (Public Library of Science (PLoS), 2021)
Onchocerca lupi (Spirurida: Onchocercidae) is a filarial worm parasitizing domestic carnivores and humans. Adult nematodes usually localize beneath in the sclera or in the ocular retrobulbar of infected animals, whilst microfilariae are found in the skin. Therefore, diagnosis of O. lupi is achieved by microscopic and/or molecular detection of microfilariae from skin biopsy and/or surgical removal of adults from ocular tissues of infected hosts. An urgent non-invasive diagnostic tool for the diagnosis of O. lupi in dog is mandatory. In this study, an immunoproteomic analyses was performed using a combination of immunoblotting and mass spectrometry techniques. Onchocerca lupi major antigen (Ol-MJA) and paramyosin (Ol-PARA) proteins were identified as potential biomarkers for serodiagnosis. Linear epitopes were herein scanned for both proteins using high-density peptide microarray. Sera collected from dog infected with O. lupi and healthy animal controls led to the identification of 11 immunodominant antigenic peptides (n = 7 for Ol-MJA; n = 4 for Ol-PARA). These peptides were validated using sera of dogs uniquely infected with the most important filarioids infesting dogs either zoonotic (Dirofilaria repens, Dirofilaria immitis) or not (Acanthocheilonema reconditum and Cercopithifilaria bainae). Overall, six antigenic peptides, three for Ol-MJA and for Ol-PARA, respectively, were selected as potential antigens for the serological detection of canine O. lupi infection. The molecular and proteomic dataset herein reported should provide a useful resource for studies on O. lupi toward supporting the development of new interventions (drugs, vaccines and diagnostics) against canine onchocercosis.